2021
DOI: 10.1159/000516443
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison between Cerebroplacental Ratio and Umbilicocerebral Ratio in Predicting Adverse Perinatal Outcome in Pregnancies Complicated by Late Fetal Growth Restriction: A Multicenter, Retrospective Study

Abstract: <b><i>Introduction:</i></b> The role of cerebroplacental ratio (CPR) or umbilicocerebral ratio (UCR) to predict adverse intrapartum and perinatal outcomes in pregnancies complicated by late fetal growth restriction (FGR) remains controversial. <b><i>Methods:</i></b> This was a multicenter, retrospective cohort study involving 5 referral centers in Italy and Spain, including singleton pregnancies complicated by late FGR, as defined by Delphi consensus criteria, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Previous studies have reported a poor performance of CPR as an APO predictor except for perinatal death [25][26][27]. Furthermore, Di Mascio et al recently reported a poor performance of CPR as well as of UCA (umbilicocerebral ratio) in late-onset FGR as outcome predictors [28]. Accordingly, our analysis confirmed a low predictive performance of CPR in the SGA group.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have reported a poor performance of CPR as an APO predictor except for perinatal death [25][26][27]. Furthermore, Di Mascio et al recently reported a poor performance of CPR as well as of UCA (umbilicocerebral ratio) in late-onset FGR as outcome predictors [28]. Accordingly, our analysis confirmed a low predictive performance of CPR in the SGA group.…”
Section: Discussionsupporting
confidence: 83%
“…In Doppler studies, this is reflected in decreased resistance in these three vascular beds. "The middle cerebral artery is the vessel of choice to assess the fetal cerebral circulation because it is easy to identify, has a high reproducibility, and provides information on the brain-sparing effect" [4,5]. "The circulation in the brain is normally high impedance.…”
Section: Introductionmentioning
confidence: 99%